2016
DOI: 10.1097/md.0000000000002573
|View full text |Cite
|
Sign up to set email alerts
|

Auscultation of Velcro Crackles is Associated With Usual Interstitial Pneumonia

Abstract: Auscultation of Velcro crackles has been proposed as a key finding in physical lung examination in patients with interstitial lung diseases (ILDs), especially in idiopathic pulmonary fibrosis (IPF). However, no studies have been carried out to assess the association of Velcro crackles with other clinical variables.We evaluated a cohort of 132 patients, prospectively and consecutively included in our ILD diagnostic program at a tertiary referral center. All patients were auscultated during the physical examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
(36 reference statements)
0
21
0
5
Order By: Relevance
“…Bilateral, basal crepitations (so called "Velcro-type" cracles) identified during physical examination, especially with concomitant digital clubbing, increases the likelihood of the diagnosis [32,37]. Crepitations, although not pathognomonic, are present in about 90% of IPF patients.…”
Section: Clinical Picturementioning
confidence: 99%
“…Bilateral, basal crepitations (so called "Velcro-type" cracles) identified during physical examination, especially with concomitant digital clubbing, increases the likelihood of the diagnosis [32,37]. Crepitations, although not pathognomonic, are present in about 90% of IPF patients.…”
Section: Clinical Picturementioning
confidence: 99%
“…Automated interpretation of lung sounds is another potential measure of disease progression in IPF. "Velcro" crackles at baseline, measured by digital auscultation, are associated with the presence of UIP in patients with ILD [57]. A prospective pilot study found that longitudinal changes in lung sounds were associated with clinical deterioration in patients with IPF [58].…”
Section: When To Initiate Treatmentmentioning
confidence: 99%
“…A subjective assessment of Velcro-like crackles bilaterally on chest auscultation predicts the presence of fibrotic ILD and usual interstitial pneumonia patterns on HRCT (10,11), and is associated with varying degrees of different ILAs (10). Hence, Velcro-like crackles may provide a rationale for investigating lung sounds to accurately identify patients with ILD, and could even be used as a screening aid.…”
Section: Rationale For the Use Of Digital Lung Auscultationmentioning
confidence: 99%